English 1 : Introduction to college English - Baraceros, Esther L. (Manila, 2009)
This book focuses on the following aspects of teaching and learning English, english vocabulary expansion through different vocabulary-building strategies, reading comprehension improvement through reading activities, linguistic or grammatical competence through contextual or situational applications, oral and written discourse competence and interpersonal-relationship development through interactive collaborative communication.
Keywords: English language- study and teaching